2015
DOI: 10.1155/2015/984706
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution Coupled with Retrotransposon Exaptation Allowed for the Generation of a Human-Protein-Specific Coding Gene That Promotes Cancer Cell Proliferation and Metastasis in Both Haematological Malignancies and Solid Tumours: The Extraordinary Case ofMYEOVGene

Abstract: The incidence of cancer in human is high as compared to chimpanzee. However previous analysis has documented that numerous human cancer-related genes are highly conserved in chimpanzee. Till date whether human genome includes species-specific cancer-related genes that could potentially contribute to a higher cancer susceptibility remains obscure. This study focuses on MYEOV, an oncogene encoding for two protein isoforms, reported as causally involved in promoting cancer cell proliferation and metastasis in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(85 reference statements)
0
14
0
Order By: Relevance
“…NYCM , a de novo gene unique to humans and chimpanzees, regulates the pathogenesis of neuroblastomas in mouse models [133], and the primate-specific PART1 , an lncRNA gene, has been identified as both a tumor suppressor and an oncogene in different contexts [44, 134, 135]. Several other human- or primate-specific de novo genes, including PBOV1 [136] , GR6 [137, 138] , MYEOV [139] , ELFN1-AS1 [140], and CLLU1 [45] , are also linked to cancer. Some have even suggested considering tumor-specifically expressed, evolutionary novel genes as their own class of genetic elements, noting that many such genes are under positive selection and may be neofunctionalized in the context of tumors [140].…”
Section: De Novo Gene Birth and Human Healthmentioning
confidence: 99%
“…NYCM , a de novo gene unique to humans and chimpanzees, regulates the pathogenesis of neuroblastomas in mouse models [133], and the primate-specific PART1 , an lncRNA gene, has been identified as both a tumor suppressor and an oncogene in different contexts [44, 134, 135]. Several other human- or primate-specific de novo genes, including PBOV1 [136] , GR6 [137, 138] , MYEOV [139] , ELFN1-AS1 [140], and CLLU1 [45] , are also linked to cancer. Some have even suggested considering tumor-specifically expressed, evolutionary novel genes as their own class of genetic elements, noting that many such genes are under positive selection and may be neofunctionalized in the context of tumors [140].…”
Section: De Novo Gene Birth and Human Healthmentioning
confidence: 99%
“…2011 ), as well as involvement in diseases, such as cancer ( Samusik et al. 2013 ; Papamichos et al. 2015 ; Guerzoni and McLysaght 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study of multiple animal genomes reported that the MYEOV gene is unique among primates only in Catarrhini. The report also notes that MYEOV has a very unusual feature as a cancer-related gene: the amino acid sequence significantly differs between humans and apes [ 13 ]. Analysis of MYEOV expression levels and promoter methylation status in several cancers in the TCGA showed that the promoter region was hypermethylated in normal tissues, while some tumors showed hypomethylation and overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological role of MYEOV is poorly understood. This may be due in part to the fact that MYEOV is an acquired gene in primates [ 13 ], making it difficult to conduct carcinogenesis in mouse models.…”
Section: Introductionmentioning
confidence: 99%